Speciation of platinum‐benzoylthiourea in the gas phase using electrospray ionization mass spectrometry and density functional theory. (10th April 2013) - Kumar, Pranaw; Jaison, P. G.; Sundararajan, Mahesh; Telmore, Vijay M.; Ghosh, Swapan K.; Aggarwal, Suresh K.
<x xml:space="preserve">Abstract</x> RATIONALE Determining the speciation of platinum‐benzoylthiourea (Pt‐BTU) in the gas phase is a challenging task due to various reaction pathways and the conformational flexibility of the BTU ligand. METHODS Electrospray ionization mass spectrometry (ESI‐MS) experiments and density functional theory (DFT) based calculations were carried out to shed light on this complex reaction in the gas phase using K2PtCl4 salt and BTU. Various Pt complexes were studied in both positive and negative ion modes of ESI‐MS using a quadrupole‐time‐of‐flight mass spectrometer. The effects of the ESI‐MS experimental parameters such as capillary voltage, pH and electrolyte on the peak intensity of the Pt‐BTU complex were investigated. DFT calculations employing B3LYP functional with the 6‐311++G** basis set were used to characterize the geometric parameters and fragmentation patterns of various Pt complexes in the gas phase. RESULTS In the positive ion mode, complexes with differing numbers of BTU ligands coordinated to the metal ion were observed, whereas, in the negative ion mode, no species associated with BTU or with the solvent (acetonitrile) molecules were found. It was also found that Pt forms complexes with the BTU ligand in different stoichiometric ratios. For both Pt(BTU)2 and Pt(BTU)3 complexes, the BTU ligand undergoes deprotonation followed by bi‐dentate coordination. DFT calculations suggest that BTU can coordinate to Pt in both cis and trans isomeric forms, which are nearly iso‐energetic with a slight preference towards the trans‐isomer. The preference of trans‐BTU binding is attributed to the exclusive retention of intra‐molecular hydrogen bonding which is absent in the cis‐form. CONCLUSIONS Experimental and theoretical calculations have shown that the gas‐phase interaction of BTU to Pt is very complex. The BTU ligand can coordinate to Pt in both mono‐dentate and bi‐dentate modes, the latter mode being favorable upon deprotonation of the BTU ligand. Furthermore, many close lying species with different geometric isomeric forms are found to be possible due to the presence of intra‐ and inter‐molecular hydrogen bonding. Copyright © 2013 John Wiley & Sons, Ltd.